Aberration correction in 3D transthoracic echocardiography - Svein-Erik Måsøy; Bastien Dénarié; Anders Sørnes; Espen Holte; Bjørnar Grenne; Torvald Espeland; Erik Andreas Rye Berg; Ole Marius Hoel Rindal; Wayne Rigby; Tore Bjåstad (WFUMB Ultrasound Open)
Three-dimensional cardiac imaging has been available in the clinic for more than two decades. Continuous improvement in image quality has occurred in this period due to the development of probe technology and beamforming techniques. The purpose of this article is to quantitatively and qualitatively analyze the effect of a commercially available aberration correction algorithm on clinically acquired 3D transthoracic echocardiography (3D TTE) images. Clinical triplane and 3D volume cineloops of at least one cardiac cycle of pre-beamformed channel data were captured from 50 patients using a GE HealthCare Vivid E95 system with the 4Vc-D matrix array probe. This resulted in a total of 3200 vol and 3136 triplane frames. The data were post-processed with and without aberration correction. Quantitatively, assessed by an image quality parameter based on coherence, all recordings were improved by aberration correction compared to those without aberration correction. Triplane data obtained a larger improvement in image quality than volume data. Qualitatively, as demonstrated by case examples, aberration-corrected images appear sharper, have a brighter tissue signal compared to the cavity, and provide better delineation of cardiac structures. 3D rendering of valves can also be significantly improved. In general, aberration correction provides a systematic improvement in clinical cardiac triplane and 3D volume images.